Pengaruh Learning Organization, Kualifikasi Pendidikan, dan Pengalaman Kerja terhadap peningkatan Kinerja Karyawan di Balai Penelitian dan Pengembangan Sumber Daya Lahan Pertanian (BBSDLP) Bogor Khususnya di Bidang Pelayanan Publik - Matturungan, Nur Hasbullah; Kurniawati, Ria; Sukmawati, Anggraini (Jurnal Aplikasi Manajemen, 2016)
Abstract: This study isex postfactowhich aims to determinethe effect ofa learning organization, educational qualifications and work experienceto increasethe performance of employees in Researchand Development Center for Agricultural Land Resources (BBSDLP) Bogor, especially inthe field ofpublic service. The results showed that the learning organization, educational qualification, work experience and togetherhave a significant effecton performance. Partially, learning organization and work experience have a significant effect while the educational qualification isopposite.